Handgrip strength in medical students: Correlation with body mass index and hand dimensions - Al-Asadi, Jasim N (Asian Journal of Medical Sciences, 2018)
Background: Handgrip is a predictor of physical fitness, hand functions, and nutritional status. It is affected by many factors including age, sex, body mass index, and hand dimensions.Aims and Objectives: To assess the handgrip strength among medical students and to examine its correlation with body mass index and hand dimensions.Materials and Methods: This cross-sectional study included 256 students of both sexes selected from College of Medicine, Basrah University, Iraq using non-probability purposive sampling method. Their anthropometric parameters including height, weight, and hand dimensions were assessed using routine techniques. The handgrip was measured by using a handheld dynamometer. Hand preference was determined by asking which hand was used to write.Results: The mean age of the participants was 21.1 ± 1.9 years. The mean of handgrip strength was 34.1 ± 11.9 Kg. Males had significantly (P